Rethinking pathways to well-being: the function of faith practice in distress alleviation among displaced Muslim women affected by war - Rutledge, Kathleen (Frontiers in Psychiatry, 2025)
BackgroundFor many populations globally, coping approaches employed during times of extreme adversity are rooted in religious convictions. Positive religious coping following potentially traumatic events and in times of crisis is widely evidenced as resilience promoting. Despite international mandates for aid and mental health responses to enable such coping, there is limited guidance for work with distinct faith groups and limited quantitative evidence overall. This mixed methods study examined the role of faith in mental health among displaced Muslim women affected by conflict, highlighting implications for responders.MethodsA total of 160 questionnaires, 50 interviews, and four focus groups were conducted among 160 Sunni Muslim women in an Iraqi internally displaced persons (IDP) camp with subjects who had been affected by the Islamic State of Iraq and Syria (ISIS) conflict. A total of 19 faith leaders, MHPSS providers, and humanitarian workers were interviewed as key informants. Qualitative responses were analyzed using inductive thematic analysis, while statistical tests examined variable correlations between the mean scores of response groups.ResultsReligious meanings were attributed to every aspect of daily life, in addition to shaping fundamental understandings of wellbeing, the ultimate goals of life, and the coping strategies employed. Religiosity was high. Prayer, reciting, or reading the Qur’an, and fasting were widely reported as a means of comfort, stress relief, divine protection, and daily provision. The function of faith practices in distress alleviation was mediated by the individual’s beliefs regarding the afterlife and by their perception of God’s “care” for their life and situation. Self-appraised “inadequate” faith practice—seen as incompatible with the fundamental goal of life for many in the study, entering Paradise after death—and feeling that God does not “care”, were variables associated with higher distress and poor mental health. Gender-blind approaches in the camp and exclusion of faith needs from assessments and response actions compounded distress by creating access barriers. Ensuring access to gender- and faith-sensitive coping resources (when requested by the affected individuals) is likely to boost mental health outcomes, particularly when such supports align with recovery and/or strengthening of the individual’s sense of connectedness to a benevolent, responsive God.